1997
DOI: 10.1115/1.2802389
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Methods for the Force Reflection of Contact

Abstract: An important problem in the field of force-reflecting systems and telerobotics is poor rendering of contact, particularly of contact with stiff surfaces. There are numerous possible sources of poor performance, including poor contact models, sampling errors, and delays due to computation or data transmission. In this paper we examine effects due to sample-and-hold, which is a fundamental property of both the discrete domain and also of the sensors and power amplifiers used in a force-reflecting system. We prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…A frictional model for penaltybased simulation was proposed in [14], and we adopt their frictional model in our work. Many authors improved the definition of penetration depth and temporal stability of penalty forces [15], [16], [17]. Stiff springs can be replaced for potential barriers [18], or integrated at a higher rate than the rest of the system [19].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…A frictional model for penaltybased simulation was proposed in [14], and we adopt their frictional model in our work. Many authors improved the definition of penetration depth and temporal stability of penalty forces [15], [16], [17]. Stiff springs can be replaced for potential barriers [18], or integrated at a higher rate than the rest of the system [19].…”
Section: Related Workmentioning
confidence: 99%
“…We then find its connected components (contact islands) [39]. The contact islands are decoupled from each other in (15) and are solved independently, which often greatly decreases the system solve time.…”
Section: Contact Between Many Rigid Objectsmentioning
confidence: 99%
“…That these two signals are not the same is cause for loss of passivity of a complete system, even when the combination of and represents a passive system, termed here the "nominal system." This spurious energy production was called "energy leak" [10], or "energy error" [9]. We can express the combined effects of zero-order hold conversion and computational delay by (3) where is the sampling period and is a pulse otherwise.…”
Section: Human Operatormentioning
confidence: 99%
“…Gillespie and Cutkosky [16] developed controllers based on half-sample predictions and based on the design in the digital domain to eliminate "energy leaks" in the system. Ellis et al [17] suggested a sampleestimate-hold concept and a suite of numerical methods to improve the performance of force reflections. Lu and Song [18] developed an energy-compensating control method to improve haptic system performance through calculating and eliminating "work difference" between the sampleddata haptic system and an ideal continuous-time haptic system.…”
Section: Related Workmentioning
confidence: 99%
“…As in [17], the maximum stiffness Kmax is defined as the maximum value of spring stiffness K under which the human operator cannot cause the system to be unstable with any free behaviours. Considering the fdevice of the DHD is around 4.0 KHz (Table 1), the maximum number of haptic threads was set to four conservatively.…”
Section: Maximum Achievable Stiffnessmentioning
confidence: 99%